Effects of electron irradiation on the phase and microstructure of TiO 2 added Bi2Sr2CaCu2O8 (Bi-2212) superconductor ceramics - Hamid N.A.; Abdullah Y.; Mohd Razif S.K.; Nizam Asbullah M.S. (2023)
For high-temperature superconductors to be used in engineering applications, the compounds must be fabricated into composite elements with the required microstructure to provide mechanical strength. Titanium oxide having very high melting point with low heat capacity, is an excellent candidate for reinforcement of brittle materials such as superconductor ceramics. In addition to high melting point, TiO2 is also capable of establishing flux pinning centers in Bi-2212 superconductor compounds. As such, TiO2 has the characteristics to reinforce composite materials without compromising their superconducting properties. To further enhance the flux pinning properties, irradiation is one of the techniques that can be used to create the required point defects. Besides, irradiation is able to enhance the mechanical properties of ceramics materials. In this study, the effect of electron irradiation on TiO2 added Bi-2212 superconductor ceramics was studied through phase and microstructure characteristics of irradiated and non-irradiated samples. Characterizations were done by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray (EDX) analysis. The XRD patterns for both irradiated and non-irradiated samples show well-defined peaks all of which could be indexed on the basis of the Bi-2212 structure. In addition, the XRD patterns indicate that electron irradiation of 100 kGray enhanced the Bi-2212 superconducting phase in the compounds. Results of SEM micrographs show improvement in the texture of the microstructure for samples that are subjected to electron irradiation of 100 kGray. The grains are seen to align in much lower degree of orientation. 2013 AIP Publishing LLC.